2008
DOI: 10.1186/1744-9081-4-43
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and subcortical anatomy of chronic spatial neglect following vascular damage

Abstract: Background: The role of the inferior parietal lobule (IPL) and superior temporal gyrus (STG) or subcortical pathways as possible anatomical correlates of spatial neglect is currently intensely discussed. Some of the conflicting results might have arisen because patients were examined in the acute stage of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 38 publications
2
50
0
1
Order By: Relevance
“…4c). These findings are highly consistent with previous studies examining the anatomy of spatial neglect (Vallar and Perani, 1986;Mort et al, 2003;Golay et al, 2008); the lesions of our patients were thus representative of the common lesion sites in spatial neglect.…”
Section: Lesion Comparisonssupporting
confidence: 92%
See 1 more Smart Citation
“…4c). These findings are highly consistent with previous studies examining the anatomy of spatial neglect (Vallar and Perani, 1986;Mort et al, 2003;Golay et al, 2008); the lesions of our patients were thus representative of the common lesion sites in spatial neglect.…”
Section: Lesion Comparisonssupporting
confidence: 92%
“…Lesion overlap studies located the critical region responsible for spatial neglect in the inferior parietal cortex (Vallar and Perani, 1986;Mort et al, 2003;Golay et al, 2008), whereas Karnath et al (2004) attributed a similar role to the central sectors of the superior temporal gyrus. In contrast, Doricchi and Tomaiuolo (2003) emphasized the role of frontoparietal disconnection as possible anatomical basis of spatial neglect.…”
Section: Discussionmentioning
confidence: 99%
“…Spatial neglect most often results from damage to perisylvian structures of the right hemisphere, including the temporal-parietal junction (Golay et al, 2008;Mort et al, 2003), the superior temporal gyrus (Karnath et al, 2004), and the inferior premotor cortex (Rengachary et al, 2011). In addition, the activity of the right posterior parietal cortex (PPC), as measured with functional MRI, is significantly decreased in patients with acute neglect (Corbetta et al, 2005).…”
Section: Transcranial Magnetic Stimulation and Spatial Attentionmentioning
confidence: 99%
“…Interestingly, in a previous study, Shapiro et al demonstrated that patients with lesions to the STG and inferior parietal lobe had evidence of a prolonged AB effect compared to those without (Shapiro, et al, 2002). The subtraction analysis that we carried out would suggest that patients with STG damage have an attentional capacity deficit that is not modifiable by behavioural intervention, and we note that damage to this region has previously been associated with prolonged neglect (Golay, Schnider, & Ptak, 2008;Karnath, Rennig, Johannsen, & Rorden, 2011). However, we note that this anatomical subtraction analysis is based on a preliminary result from a post hoc analysis, and as such, requires further examination before any firm conclusions can be drawn.…”
Section: Recovered Versus Ongoing Neglectmentioning
confidence: 48%